CORRELATING THE CONTENT AND CONTEXT OF PAS 55 WITH THE ISO 55000 SERIES - van den Honert, A F; Schoeman, J S; Vlok, P J (The South African Journal of Industrial Engineering, 2013)
The ISO 55000 series is soon to supersede PAS 55 as the most recognised international standard for asset management. A correlation of the content and context of PAS 55 with the ISO 55000 series is required to assist organisations with the transition. After analysis of the structures, similarities, differences, and omissions of the two standards, a map was created to correlate the summarised content and context. The map established that, although both sets of standards have a similar structural framework, the ISO 55000 series is a more comprehensive and detailed standard, creating a clearer way to implement an asset management system within an organisation.